2021
DOI: 10.7759/cureus.19472
|View full text |Cite
|
Sign up to set email alerts
|

“Vascular” Korsakoff Syndrome With Bilaterally Damaged Mammillothalamic Tracts: Insights Into the Pathogenesis of “Acute” Korsakoff Syndrome As Acute-Onset Irreversible Anterograde Amnesia

Abstract: The structural pathogenesis of Wernicke-Korsakoff syndrome remains debatable. Wernicke encephalopathy is acute and often reversible whereas Korsakoff syndrome (KS) is chronic and may be irreversible. The cognitive deficits observed in KS are considered to be primarily due to damage to the anterior nucleus of the thalamus, mammillary bodies, and corpus callosum. We present an extremely rare case of non-alcoholic “vascular” KS (vKS) as acute-onset amnesia. A 97-year-old man living alone was brought to our hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The MTT effectively connects the mammillary bodies, which itself receives input from the hippocampus, to the anterior thalamic nuclei (ATN) 39 . Lesions to the MTT bilaterally, accompanied by damage to the ATN, have been sufficient to cause acute and irreversible memory disorder that is very similar to alcoholic KS 40 .…”
Section: Ad Comparison Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MTT effectively connects the mammillary bodies, which itself receives input from the hippocampus, to the anterior thalamic nuclei (ATN) 39 . Lesions to the MTT bilaterally, accompanied by damage to the ATN, have been sufficient to cause acute and irreversible memory disorder that is very similar to alcoholic KS 40 .…”
Section: Ad Comparison Resultsmentioning
confidence: 99%
“…The MTT effectively connects the mammillary bodies, which itself receives input from the hippocampus, to the anterior thalamic nuclei (ATN) 39 . Lesions to the MTT bilaterally, accompanied by damage to the ATN, have been sufficient to cause acute and irreversible memory disorder that is very similar to alcoholic KS 40 . Furthermore, another study 41 showed that 7 out of 12 patients with thalamic infarct who had damage to the MTT performed worse in verbal episodic memory task than the 5 patients with preserved MTT.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT effectively connects the mammillary bodies, which itself receives input from the hippocampus, to the anterior thalamic nuclei [45]. Lesions to the MTT bilaterally, accompanied by damage to the anterior thalamic nuclei, have been sufficient to cause acute and irreversible memory disorder that is very similar to KS [46]. Furthermore, another study [47] showed that 7 out of 12 patients with thalamic infarct who had damage to the MTT performed worse in the verbal episodic memory task than the 5 patients with preserved MTT.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that amnesia is produced after bilateral lesions to any of these sites (72)(73)(74)(75)(76)(77)(78). However, they have also shown that there can be some variation in the nature of the amnesia and its associated presentation.…”
Section: Psychoanalysis and Amnesiamentioning
confidence: 99%